2016
DOI: 10.1158/1078-0432.ccr-15-1268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 5-Marker Blood Test for Colorectal Cancer Early Detection in a Colorectal Cancer Screening Setting

Abstract: Purpose: In initial studies that included colorectal cancer patients undergoing diagnostic colonoscopy, we had identified a serum marker combination able to detect colorectal cancer with similar diagnostic performance as fecal immunochemical test (FIT). In this study, we aimed to validate the results in participants of a large colorectal cancer screening study conducted in the average-risk, asymptomatic screening population.Experimental Design: We tested serum samples from 1,200 controls, 420 advanced adenoma … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 34 publications
3
74
0
Order By: Relevance
“…Moreover, FAPα combined with the three traditional biomarkers improved the sensitivity (41.5%) without compromising specificity (95.0%) for ESCC detection. Our data were consistent with those studies in which FAPα improved the diagnostic value of CRC [45]. These results showd the screen value of FAPα for ESCC, and demonstrated that the combination of FAPα and the three traditional biomarkers can detect about 40% ESCC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, FAPα combined with the three traditional biomarkers improved the sensitivity (41.5%) without compromising specificity (95.0%) for ESCC detection. Our data were consistent with those studies in which FAPα improved the diagnostic value of CRC [45]. These results showd the screen value of FAPα for ESCC, and demonstrated that the combination of FAPα and the three traditional biomarkers can detect about 40% ESCC.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, circulating fibroblast activation protein α (FAPα) shows good specificity for colorectal cancer (CRC) diagnosis, and the combination of FAPα and other multiple markers all show high sensitivity for early detection of CRC [45]. Circulating FAPα levels were demonstrated significantly lower in cancer patients compared with healthy subjects and correlated inversely with survival in most types of cancer [69].…”
Section: Introductionmentioning
confidence: 99%
“…if polyps)NoWerner et al (2016) [9]RetrospectiveCEAFerritin Seprase Osteoponti nAnti-p5336 CRC420 advanc ed adenom a, 1200 controlsSerum0.7844%90%NDYes (CEA sens 50%, spec 90%)Yes (early cancers were detected at least as well as late-stage)NoCEA + anti-p530.8558%90%Wang et al (2016) [61]ProspectiveCOL3A186 CRC21 enteritis, 3 polyps, 68 normalPlasmaEpithelial tissue0.920.97598.8%95.2%69.1%91.1%54.23 ng/m LYes (CEA: AUC 0.791, sens 70.2%, spec 73%)YesYes (mRNA)Rho et al (2016) [22]RetrospectiveBAG4 IL6ST** VWFEGFRBAG4 IL6ST VWFCD4460 CRC60 adenom as, 30 controlPlasma/Serum0.810.7940.9%42.44%90%NDNoNoYesOverholt et al (2016) [22]ProspectiveCA11-19131 CRC, 65 polyps, 182 benign disease, 103 controlsSerumND98%84%6.4 units/mLNoNoNoGezer et al (2015) [62]ProspectiveTrimethylations of lysine 9 on histone 3 (H3K9me3)Trimethylations of lysine 20 on histone 4 (H4K20me3)63 CRC40 cancer-freePlasmaNo significant difference between CRC and controls 0.715ND14.3%Yes95%NoNo…”
Section: Resultsmentioning
confidence: 99%
“…Non-invasive tests could increase participation in CRC screening programs and interest in the identification of suitable biomarkers is growing [8], but only a few were validated in a screening setting: the most advanced blood test so far, based on the detection of cell-free methylated SEPT9 in plasma, achieved a sensitivity (specificity) of 48% (92%) for the detection of CRC [9]. The combination of two other markers, CEA and anti-TP53 antibody, also evaluated in the BLITZ study (albeit not using the same samples as in the current analysis), achieved a sensitivity (specificity) of 58% (90%) [15]. Stool tests represent another non-invasive alternative.…”
Section: Discussionmentioning
confidence: 83%